Meis transcription factors regulate cardiac conduction system development and adult function - Muñoz-Martín, Noelia; Simon-Chica, Ana; Díaz-Díaz, Covadonga; Cadenas, Vanessa; Temiño, Susana; Esteban, Isaac; Ludwig, Andreas; Schormair, Barbara; Winkelmann, Juliane; Olejnickova, Veronika; Sedmera, David; Filgueiras-Rama, David; et al. (Cardiovascular research, 2025)
AIMS: The cardiac conduction system (CCS) is progressively specified during development by interactions among a discrete number of transcription factors (TFs) that ensure its proper patterning and the emergence of its functional properties. Meis genes encode homeodomain TFs with multiple roles in mammalian development. In humans, Meis genes associate with congenital cardiac malformations and alterations of cardiac electrical activity; however, the basis for these alterations has not been established. Here, we studied the role of Meis TFs in cardiomyocyte development and function during mouse development and adult life. METHODS AND RESULTS: We studied Meis1 and Meis2 conditional deletion mouse models that allowed cardiomyocyte-specific elimination of Meis function during development and inducible elimination of Meis function in cardiomyocytes of the adult CCS. We studied cardiac anatomy, contractility, and conduction. We report that Meis factors are global regulators of cardiac conduction, with a predominant role in the CCS. While constitutive Meis deletion in cardiomyocytes led to congenital malformations of the arterial pole and atria, as well as defects in ventricular conduction, Meis elimination in cardiomyocytes of the adult CCS produced sinus node dysfunction and delayed atrio-ventricular conduction. Molecular analyses unravelled Meis-controlled molecular pathways associated with these defects. Finally, we studied in transgenic mice the activity of a Meis1 human enhancer related to an single-nucleotide polymorphism (SNP) associated by Genome-wide association studies (GWAS) to PR (P and R waves of the electrocardiogram) elongation and found that the transgene drives expression in components of the atrio-ventricular conduction system. CONCLUSION: Our study identifies Meis TFs as essential regulators of the establishment of cardiac conduction function during development and its maintenance during adult life. In addition, we generated animal models and identified molecular alterations that will ease the study of Meis-associated conduction defects and congenital malformations in humans.
Keywords: Myocardial Contraction; Heart Conduction System; Cardiac development; Sinoatrial Node; kardiomyocyty; akční potenciály; Transcription factor; Heart Rate; věkové faktory; Phenotype; převodní systém srdeční; nodus sinuatrialis; Myocytes, Cardiac; zvířata; Homeodomain Proteins; Action Potentials; vrozené srdeční vady; myši knockoutované; Gene Expression Regulation, Developmental; Mouse targeted mutation; srdeční frekvence; Mice, Knockout; PR elongation; Myeloid Ecotropic Viral Integration Site 1 Protein; srdeční arytmie; fenotyp; homeodoménové proteiny; kontrakce myokardu; Sinus node dysfunction; Arrhythmias, Cardiac; vývojová regulace genové exprese; Animals; Age Factors; transkripční faktor Meis1; Heart Defects, Congenital